CONTRIBUTION TO THE COMPARATIVE STUDY OF WATER QUALITY OF DIFFERENT AQUIFERS IN THE EL OUED REGION (SOUF) - Djamel Besser, Ali Ghomri* (university of eloued جامعة الوادي, 2024)
The aquifer system in the El-Oued region consists of three aquifers: the unconfined aquifer (phreatic), and two confined aquifers (the terminal complex aquifer and the interlayer continental aquifer). These aquifers are considered as a single water resource available in this region. Despite this wealth, the quality of these waters remains generally mediocre to bad quality. The contribution to the comparative study of the physico-chemical quality of waters from different aquifers in the Souf region reveals, in general, high mineralization (mainly originating from the geological nature of the surrounding formations) decreasing with depth, and exceeding the standards recommended by the WHO. Therefore, strict criteria must be demanded to improve the chemical quality of water and ensure its potability according to national and international standards before supplying it to consumers.
Keywords: Terminal Complex; Interlayer Continental; phreatic; Mineralization; Physico-chemical quality